MicroRNA-26b suppresses tumorigenicity and promotes apoptosis in small cell lung cancer cells by targeting myeloid cell leukemia 1 protein - Jin-Guo Yu; Cheng-Hong Ji; Min-Hua Shi (Kaohsiung Journal of Medical Sciences, 2018)
The aim of this study was to investigate the role of microRNA-26b (miR-26b) in regulating the proliferation, migration, and apoptosis of small cell lung cancer (SCLC) cells. First, we examined the expression level of miR-26b in human normal fetal lung fibroblasts (NFLFs) and three SCLC cell lines NCI-H466, NCI-H1688, and NCI-H196. In the following experiments, the three SCLC cell lines were transfected with miR-26b mimic and inhibitor. Cell growth and survival, as well as migration and invasion capacities were determined by MTT, colony formation, Transwell migration and invasion, and wound healing assays. Cell apoptosis, production of reactive oxygen species, and mitochondrial membrane potential were also measured in the three cell lines following various treatments. As a result, we found that the level of miR-26b was significantly lower in SCLC cells than in NFLFs. Additionally, transfection with miR-26b mimic could inhibit proliferation, colony formation, and migration, as well as induce apoptosis in these SCLC cell lines; while miR-26b inhibitor showed the opposite effects. Further mechanistic experiment revealed that miR-26b could suppress the expression of myeloid cell leukemia 1 protein (Mcl-1) and the 3′-untranslated region (3′-UTR) of Mcl-1 may be the direct binding site of miR-26b, suggesting that the effect of miR-26b may be mediated by targeting Mcl-1. Collectively, our findings offer a new insight into the role of miR-26b in the pathogenesis of SCLC, and provide primary evidence supporting the potential of miR-26b-based therapy for the treatment of SCLC. Key words: miR-26b, Tumorigenicity, Small cell lung cancer, Apoptosis, Myeloid cell leukemia 1 protein